Las balas matan, pero la indiferencia contramata (2021)
A study by Professor Gloria María Gallego, from the School of Law, analyzes the spiral of violence, revenge and hatred in which, as of August, 284 ex-combatants of the Revolutionary Armed Forces of Colombia (FARC) had been murdered. The figure becomes a mere statistic that goes unnoticed in the face of indifference and, often, indolence of society.